Co-producing justice sanctions? Citizen perspectives. (September 2016) - McCulloch, Trish; ,
This article is about the place of those sentenced in criminal justice sanctions. Specifically, it reports on the findings of a co-productive qualitative inquiry that sought to explore the place and possibility of service user co-production within justice sanctions, drawing on the experience of people with convictions. The conclusion of the article is that participation and co-production matters in justice sanctions. The detail and implications of this conclusion are discussed.